The effect of an aminoalcohol on the polymerization of acrylates with type II initiators - Karasu, Feyza; Arsu, Nergis (SPRINGER, 2011)
In this study, the authors report the use of an aliphatic amine and an aromatic aminoalcohol as synergists with various Type II initiators by using Photo-DSC (Photo-differential scanning calorimetry) technique. The photopolymerization of triacrylate and diacrylate was performed under nitrogen atmosphere in the presence of an amine or aminoalcohol with type II initiators, which allowed us to compare the efficiency of the initiating radicals. The oxygen scavenging role of the amine was left out.
Keywords: Photopolymerization; Free radical polymerization; Photo-differential scanning calorimetry; Synergist; Type II photoinitiator; FREE-RADICAL POLYMERIZATION; ELECTRON-TRANSFER; PHOTOINITIATION; AMINES; Thermodynamics; Chemistry